The Taman Detachment of the Bosporan Expedition of IIMK RAS, 2006–2013 - Kashaev, Sergey (Hyperboreus, 2015)
A survey of the excavations at the necropolis and settlement-site of Artyushchenko-2, rural sites of Vyshesteblievskaya-11 and Vyshesteblievskaya-3 (the Southern part of the Taman Peninsula) conducted by the Taman team of the Bosporan Expedition of the Institute of the History of Material Culture (IIMK), RAS, 2006–2013.